Première évaluation Paléoépidémiologique d’une série ostéoarchéologique de la côte centrale Péruvienne : le site d’Ancón 1 - Claudi M. Rojas-Sepúlveda; Olivier Dutour (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In this study, we analyzed the osteological remains of 121 individuals coming from the pre-Columbian site of Ancón I on the Peruvian Central Coast. Frequencies of pathological conditions were established taking into account the state of preservation. Degenerative Joint Disease (DJD) was the most frequently found disease. Among the 119 individuals that can be observed for this purpose, 91 (76.5%) presented lesions of DJD. The other results showed the adequacy of the diet, a high level of physical stress and environmental conditions that could have been favorable for the development of infections.